2020
DOI: 10.1038/s41598-020-68385-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal gait characteristics and ankle kinematics of backward walking in people with chronic ankle instability

Abstract: Backward walking offers a unique challenge to balance and ambulation. This study investigated the characteristics of spatiotemporal gait factors and ankle kinematics during backward walking in people with chronic ankle instability. Sixteen subjects with chronic ankle instability and 16 able-bodied controls walked on a treadmill at their self-selected speed under backward and forward walking conditions. Gait speed, cadence, double limb support percentage, stride time variability, and threedimensional ankle kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have suggested several methods to evaluate the gait function of CAI patients more accurately. For example, the modified backward walking test or faster treadmill speed test could more clearly reflect walking ability in the CAI patients than conventional gait analysis [ 30 , 31 ]. The use of these methods should be considered for future trials for CAI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested several methods to evaluate the gait function of CAI patients more accurately. For example, the modified backward walking test or faster treadmill speed test could more clearly reflect walking ability in the CAI patients than conventional gait analysis [ 30 , 31 ]. The use of these methods should be considered for future trials for CAI patients.…”
Section: Discussionmentioning
confidence: 99%
“…To compare between-group baseline characteristics, nonparametric Mann-Whitney U tests and X 2 tests were used for continuous and categorical variables, respectively. Time series data (frontal plane mean angles and normalized peroneal EMG) were plotted throughout the stance phase with their corresponding 95% confidence intervals (CI) [62]. A significant, meaningful difference was defined in case a nonoverlapping CI was demon-strated for consecutive 3% of the stance [62,63].…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…Time series data (frontal plane mean angles and normalized peroneal EMG) were plotted throughout the stance phase with their corresponding 95% confidence intervals (CI) [62]. A significant, meaningful difference was defined in case a nonoverlapping CI was demon-strated for consecutive 3% of the stance [62,63]. Additionally, a 2 × 2 mixed analysis of variance (ANOVA) was conducted using Statistical Parametric Mapping (SPM), to compare the between-group (group), within-group (time), and interaction (group × time) effects on the ankle's frontal plane angle and muscle activation normalized amplitude.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…These detailed descriptions can also assist physiotherapists to improve their rehabilitation treatment and help designers develop rehabilitation-assistive products [ 7 9 ]. Gait analysis using motion tracking data allows scientists to understand posture control and force application of the foot during walking [ 10 , 11 ]. For example, Chinn et al found that subjects with ankle instability experienced more inversions during jogging than walking [ 12 ].…”
Section: Introductionmentioning
confidence: 99%